2022
DOI: 10.3389/fpls.2022.938570
|View full text |Cite
|
Sign up to set email alerts
|

RNA structure mediated thermoregulation: What can we learn from plants?

Abstract: RNA molecules have the capacity to form a multitude of distinct secondary and tertiary structures, but only the most energetically favorable conformations are adopted at any given time. Formation of such structures strongly depends on the environment and consequently, these structures are highly dynamic and may refold as their surroundings change. Temperature is one of the most direct physical parameters that influence RNA structure dynamics, and in turn, thermosensitive RNA structures can be harnessed by a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…At elevated temperatures, the translation of PHYTOCHROME-INTERACTING FACTOR 7 ( PIF7 ), HEAT SHOCK FACTOR A2 ( HSFA2 ) and WRKY22 was enhanced. The expression levels of these transcription factors control plant thermomorphogenesis, heat acclimation and other stress responses ( 76 , 77 ). The discovery of RNA thermometers in photosynthetic eukaryotes opens up new research directions in thermoregulation and new biotechnological applications in plants and algae.…”
Section: Discussionmentioning
confidence: 99%
“…At elevated temperatures, the translation of PHYTOCHROME-INTERACTING FACTOR 7 ( PIF7 ), HEAT SHOCK FACTOR A2 ( HSFA2 ) and WRKY22 was enhanced. The expression levels of these transcription factors control plant thermomorphogenesis, heat acclimation and other stress responses ( 76 , 77 ). The discovery of RNA thermometers in photosynthetic eukaryotes opens up new research directions in thermoregulation and new biotechnological applications in plants and algae.…”
Section: Discussionmentioning
confidence: 99%
“…"RNA thermometers", perhaps aided by KREH2, may regulate editing in response to shifts in temperature and intracellular conditions. Thermometers in trypanosomes, as in other systems, including in plants and chloroplast in green alga (74,75), could influence mRNA and or gRNA secondary structure, or RNA helicase conformation, masking or promoting productive RNA hybrids, cognate or non-cognate. Interestingly, temperature reduction promoted editing efficiency of some cytochrome mRNAs.…”
Section: Rna Conformation In the Nd7 3' Early Checkpoint May Hinder P...mentioning
confidence: 99%
“…Temperature is one of the most direct physical parameters that influence RNA structure dynamics, and in turn, thermosensitive RNA structures can be used by a cell to perceive and respond to its temperature environment. Indeed, many thermosensitive RNA structures (RNA thermoswitches) with biological function have been identified in bacteria and viruses (Chowdhury et al , 2006; Thomas et al , 2022), suggesting the temperature responsiveness of RNA secondary structures has been harnessed multiple times during evolution. It was shown that temperature sensitivity of RNA structures is exploited by bacteria to fabricate RNA thermosensing systems that allow a rapid adaptive response to temperature change (Mandin & Johansson, 2020).…”
Section: Variation Of Plant Noncoding Genomesmentioning
confidence: 99%